2004
DOI: 10.1242/jcs.01087
|View full text |Cite
|
Sign up to set email alerts
|

Calcium transients induce spatially coordinated increases in traction force during the movement of fish keratocytes

Abstract: The coordination of protrusion with retraction is essential for continuous cell movement. In fish keratocytes the activation of stretch-activated calcium channels, and the resulting increase in intracellular calcium, trigger release of the rear cell margin when forward movement is impeded. Although it is likely that retraction involves a calcium-dependent increase in cytoskeletal contractility, it is not known how the timing, magnitude and localization of contractile forces are organized during retraction. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
85
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 57 publications
13
85
0
Order By: Relevance
“…In general, the coordination of traction forces along the axis of movement is regulated by Ca 2+ influx through Ca 2+ channels. Traction forces are maintained via adhesion contacts until retraction occurs [9]. This is in line with observations made in fibroblasts.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In general, the coordination of traction forces along the axis of movement is regulated by Ca 2+ influx through Ca 2+ channels. Traction forces are maintained via adhesion contacts until retraction occurs [9]. This is in line with observations made in fibroblasts.…”
Section: Discussionsupporting
confidence: 89%
“…It has been shown that mechanosensitive Ca 2+ channels are involved in the coordination of the protrusion of the lamellipodium with the retraction of the rear part of migrating cells [8,9]. But so far, the molecular identity of such channels is not known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, tensile forces transmitted to neighbouring cells by mediolateral traction may activate stretch-activated calcium channels ( Jaffe 2007), and result in the propagation of contraction, development of traction force (Doyle et al 2004) and the further development of mediolaterally oriented tension. The waves of calcium transients and associated contraction waves are propagated across the IMZ explants (Wallingford et al 2001), and although they do not appear to be temporally or spatially correlated with the directions of MIB progression, or the axes of intercalation under the culture conditions in which they were observed, they may reflect a phenomenon used locally, with different timing and spatial parameters, in vivo.…”
Section: Tensile Positive Feedback Mechanisms May Enhance Mib Expresmentioning
confidence: 99%